2018
DOI: 10.12788/jhm.2918
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Monitor Alarm Rates at 5 Children's Hospitals

Abstract: Alarm fatigue has been linked to patient morbidity and mortality in hospitals due to delayed or absent responses to monitor alarms. We sought to describe alarm rates at 5 freestanding children's hospitals during a single day and the types of alarms and proportions of patients monitored by using a point-prevalence, cross-sectional study design. We collected audible alarms on all inpatient units and calculated overall alarm rates and rates by alarm type per monitored patient per day. We found a total of 147,213 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Initial studies identified alarm fatigue to be directly related to the number of alarms per patient per day, with some patients experiencing up to 350 physiological monitor alarms daily 7. On a paediatric ward, up to 99% of alarms are non-actionable, either not accurately reflecting the clinical status of the patient or not requiring intervention 1 8 9. Furthermore, nursing response time to alarms increases as exposure to non-actionable alarms increases 10.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies identified alarm fatigue to be directly related to the number of alarms per patient per day, with some patients experiencing up to 350 physiological monitor alarms daily 7. On a paediatric ward, up to 99% of alarms are non-actionable, either not accurately reflecting the clinical status of the patient or not requiring intervention 1 8 9. Furthermore, nursing response time to alarms increases as exposure to non-actionable alarms increases 10.…”
Section: Introductionmentioning
confidence: 99%
“…In the neonatal population, these limitations are particularly apparent and produce several unique adverse outcomes. The frequency of false alarms secondary to the frequent movement of newborns is associated with provider alarm fatigue, infant hearing loss, and a disruptive environment for development [ 8 , 9 , 10 , 11 , 12 ]. Additionally, the humid environment of neonatal incubators and the infant’s thin, underdeveloped skin cause the adhesive in electric leads to fail and require frequent changing.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Despite these concerns, CPMs are routinely used: up to 48% of pediatric patients in nonintensive care units at children's hospitals are monitored. 2 Although the low number of alarms that receive responses has been well-described, 8,9 the reasons why clinicians do or do not respond to alarms are unclear. A study conducted in an adult perioperative unit noted prolonged nurse response times for patients with high alarm rates.…”
mentioning
confidence: 99%